2007
DOI: 10.1111/j.1440-1746.2007.05250.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations of Wnt signaling pathway–associated genes in hepatocellular carcinoma

Abstract: These data suggest that mutation of AXIN1 gene is a frequent and late event for HCC associated with cirrhosis, and is correlated significantly with abnormal expression of axin and beta-catenin. Therefore, activation of Wnt signaling through AXIN1 rather than beta-catenin mutation might play an important role in liver carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 43 publications
0
46
0
3
Order By: Relevance
“…Besides expressing mostly at the membrane, these three members of armidillo protein family were also found in the cytoplasm or nucleus. It has been shown to be important in the development of several tumors that constitutionally activated the Wnt/Wingless signaling pathway by stabilization and accumulation of β-catenin in the nucleus and cytoplasm [24][25][26][27] . Like β-catenin, γ-catenin can also bind to APC protein and is able to translocate into the nucleus participating in the Wnt signaling pathway [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides expressing mostly at the membrane, these three members of armidillo protein family were also found in the cytoplasm or nucleus. It has been shown to be important in the development of several tumors that constitutionally activated the Wnt/Wingless signaling pathway by stabilization and accumulation of β-catenin in the nucleus and cytoplasm [24][25][26][27] . Like β-catenin, γ-catenin can also bind to APC protein and is able to translocate into the nucleus participating in the Wnt signaling pathway [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in WNT signaling components (APC, β-catenin, AXIN, WTX, TCF4) can be the cause of WNT pathway activation in these tumors. [41][42][43][44][45] In colorectal cancer, mutations in WNT signaling components have been extensively characterized. Approximately 85% of colorectal tumors have mutations in APC, whereas an activating mutation in β-catenin was observed in 50% of colorectal tumors lacking APC mutations.…”
Section: Canonical Wnt Signalingmentioning
confidence: 99%
“…Axin1 is constitutively expressed, whereas Axin2 (also known as Axil or Conductin) is induced by Wnt/β-catenin signalling and takes part in a negative feedback loop [75] . Kim et al [76] recently observed reduced Axin1 expression only in HCC tissues and not in cirrhotic nodules, implying that its reduced expression is independent of cirrhosis. There are currently no reports of Axin2 expression in HCC.…”
Section: Gsk3β Ckiα Axin and Apcmentioning
confidence: 99%
“…The TCF/LEF family has several spliced forms with unknown functional significance and it is suggested that they may activate preferential genes [86] . In HCC, mutations of TCF-4 are rare with 315 August 10, 2011|Volume 2|Issue 8| WJCO|www.wjgnet.com [70][71][72] phospho-GSK3β High 52 IHC [73] Axin1 Low 67 IHC [76] Dvl High 71 Western blotting [82] Prickle-1 Low 55 PCR [82] HDPR1 Low 58 PCR [83] PIN1 High 53 Western blotting [65] TCF-4 High 91 PCR [87] LEF-1 High 52 IHC [88] CDH17 High 72 IHC [90] CDH17: Cadherin-17; Dvl: Dishevelled; FZD: Frizzled; phospho-GSK3β: Phosphorylated glycogen synthase kinase 3β; HDPR1: Human homologue of Dapper; IHC: Immunohistochemistry; LEF: Lymphoid enhancer factor; PCR: Polymerase chain reaction; PIN1: Peptidyl-prolyl cis/trans isomerase; TCF: T-cell factor.…”
Section: Tcf/lefmentioning
confidence: 99%